2011
DOI: 10.3354/meps09381
|View full text |Cite
|
Sign up to set email alerts
|

Glass sponge reefs as a silicon sink

Abstract: Resale or republication not permitted without written consent of the publisher Aphrocallistes vastus and Heterochone calyx are reef-building glass sponges, whose heavily silicified skeletons create a large reservoir of silicon. Photo: S. P. Leys, V. Tunnicliffe, and ROPOS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 58 publications
1
52
1
Order By: Relevance
“…Sauer et al 2006;Siipola et al 2013). Some attempts have been made (Kamatani 1971;Maldonado et al 2005;Chu et al 2011), and it has tentatively been shown that even the group or species origin of the BSi may influence dissolution rates. It is likely that significant occurrence of pedogenic, amorphous Si in the Kuutsjärvi sediments would have shown up in the extraction used.…”
Section: Lithogenic Amorphous Si?mentioning
confidence: 99%
“…Sauer et al 2006;Siipola et al 2013). Some attempts have been made (Kamatani 1971;Maldonado et al 2005;Chu et al 2011), and it has tentatively been shown that even the group or species origin of the BSi may influence dissolution rates. It is likely that significant occurrence of pedogenic, amorphous Si in the Kuutsjärvi sediments would have shown up in the extraction used.…”
Section: Lithogenic Amorphous Si?mentioning
confidence: 99%
“…Recent studies have suggested the idea that siliceous sponges are relevant DSi users at a large ecological scale, a role traditionally neglected by nutrient ecologists and biogeochemists and that is biasing the advance toward a realistic understanding of silicon cycling in marine systems, and particularly on continental margins (Reincke & Barthel, 1997;Maldonado et al, 2005Maldonado et al, , 2010aMaldonado et al, , 2011Chu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…; Chu et al. ) and live in a low‐resource environment (Yahel et al. ); thus, organic‐based defences (chemicals) would be a more energetically costly strategy.…”
Section: Discussionmentioning
confidence: 99%
“…; Chu et al. ). Because of the high content of siliceous skeleton and low amounts of living tissue found in glass sponges, they are of relatively low mass‐specific nutritional value, and thus few animals are expected to feed on them (Barthel ).…”
mentioning
confidence: 97%